(untitled) (Global Journal of Science Frontier Research, 2020)
Abstruct-Grass pea can be consumed as supplementary nutrients in a diet without a neurolathyrism health problem among all classes of people in the south-central coastal area of Bangladesh. The study aimed at assessing the grass pea consumption pattern in diet and detection of neurolathyrism patients over 400 respondents among four villages. An investigation was also done on various paralytic admitted patients at hospital in the south central coastal region of Bangladesh. Among respondents of four villages 63% were male, 38.75% was illiterate, 41.5% was completed primary education and 30% of respondent’s monthly income Tk.6000-9500 was maximum. Among respondents 89.6% consumed grass pea was 1/3 or less than cereal at its proportion in a meal and they all consumed meat, fish, egg, vegetables also. In grass pea food items 25.25% respondents prefer Dal barta was maximum and Dobakhesari (snack) 0.75% was lowest. 95.75% respondent was used various spices like onion, garlic, chili, tamarind etc. with grass pea to making food items to increasing its palatability and testes.